Dung beetle community composition affects dung turnover in subtropical US grasslands. Issue 2 (22nd February 2022) - Stanbrook, Roisin; King, Joshua R.
Abstract: An important service in many ecosystems is the turnover and degradation of dung deposited by cattle. Dung beetles are the primary group of insects responsible for dung turnover, and factors affecting their abundance and distribution thus impact dung degradation. Lands lost to grazing due to dung buildup and pasture contamination total millions of acres per year in US pastures. We evaluated the structural differences in dung beetle assemblages in natural grasslands versus a managed agroecosystem in subtropical southeastern Florida (USA). We measured the direct effect of dung longevity when dung beetle fauna normally inhabiting dung pats were excluded. Our results indicate dung beetle abundance, functional diversity, and species richness have a substantial impact on the rate of dung turnover in subtropical pastoral lands with ~70% of dung removed from the soil surface after three months. Functional diversity and evenness did not have a significant positive effect on dung removal in managed, versus natural grasslands demonstrating a strong relationship between dung beetle assemblage composition and delivery of a key ecological process, dung degradation. We suggest the importance of trees, which provide a thermal refuge for beetles, should be dispersed within matrixes of open pasture areas and within proximity to adjacent closed‐canopy hammocks to facilitate the exchange of dung beetles between habitats and therefore maintain the provisioning of dung degradation services by dung beetle assemblages. Abstract : An important service in many ecosystems is the turnover and degradation of dung deposited by cattle. Dung beetles are the primary group of insects responsible for dung turnover, and factors affecting their abundance and distribution thus impact dung degradation. Our results indicate dung beetle abundance, functional diversity, and species richness has a substantial impact on the rate of dung turnover in subtropical pastoral lands with ~70% of dung removed from the soil surface after three months.